Historical blocking: CN 2022-12-22 to 2022-12-26 (China) - Voidly (2022)
CRITICAL severity censorship detected in China. Confidence: 93%. Data sourced from ooni-historical-backfill.
Censorship Incident ID: CN-2022-0352
Keywords: censorship; CN; censorship; critical